COPING MECHANISM PADA PESERTA DIDIK SD (STUDI KASUS DI SD ISLAM TERPADU MUTIARA HATI MALANG) - Budianto A (Jurnal Konseling Pendidikan Islam, 2020)
Abstract: The purpose of this study is to find the causes of coping habits in students, theoretically coping is divided into two namely problem solving focused coping and emotional focused coping, individuals using problem solving focused coping when individuals face problems that they think can be controlled such as problems -problems related to school or work while the use of emotional focused coping when individuals are faced with problems that he thinks are difficult to control. The research method used is a case study and research site at SDIT Mutiara Hati Malang, where conclusions or results from this study are students at SDIT Mutiara Hati often complain because the pattern of educating teachers in schools who do not dare to give punishment is because they are afraid to complain by the guardian of the student, and the pattern of educating parents who often indulge as if there is homework from the school students in doing homework are often assisted by parents. Keywords: Coping Mechanism, Students, Elementary School